Questions & answers on public employee negotiation - Heisel, W. D.; Hallihan, J. D. (Chicago : Public Personnel Association, 1967)
This book concerns the "nuts and bolts" of the problem of representing a public agency - city, state, school system, or special district - in its relationships with its organized employees. It is not intended as a scholarly work. Both the format of the questions and answers and the content are intended to make this a ready reference work for the less experienced practitioner in public administration.
Published in 1973 under title: New questions & answers on public employee negotiation.
Includes index.
Includes bibliographical references: p. 209.
rpm 19/02/2018
Loans
Keywords: Collective bargaining